The in-between-ness of the life narrative: negotiating disciplinary boundaries in selected Zimbabwean political narratives - Javangwe, Tasiyana (Indiana University Press, 2022)
Political life narratives have emerged in Zimbabwe and elsewhere to contest, rebut, or corroborate versions of official history on nationalist trajectories from the liberation struggles and thereafter. This development has excited new critical attention on such narratives that before were despised by historians who did not accept autobiography in general as a serious field of study that could contribute to knowledge. This discussion focuses on selected political life narratives of Zimbabwean nationalists, arguing that the life narrative is a useful entry point in understanding not only individual identities, but the history, culture, and politics of Zimbabwe. It argues that the existence of the life narrative genre in a particular culture is an important signifier of the dynamic processes of both individual and group identity conception in that society, and therefore it must be read alongside other disciplines such as history.